Pengaruh Bauran Pemasaran Terhadap Loyalitas Pelanggan Restoran Waroeng Hotplate Odon Bogor - Tobing, Tasya Amanda; Nurmalina, Rita; Jahroh, Siti (Jurnal Agribisnis Indonesia, 2021)
Currently, Indonesia has a 265 million population in which more than one-third of the population is the modern generation who are more likely to have a preference for something that simple and practical like taking a meal in the restaurant. Bogor is one of the cities generally known for its culinary varieties. Waroeng Hotplate Odon is one of them which uniquely serves dishes, which uses hot plates and has a spiciness level and its sales experienced a downward trend due to high competition among the restaurants. This research aims to analyze the effect of marketing mix consist of 7P variables which are: product, promotion, place, price, people, process and physical evidence towards customer satisfaction and customer loyalty of Waroeng Hotplate Odon restaurant. The sample of the research is 393 people who visited Waroeng Hotplate Odon restaurant. The sampling method applied in this study is purposive sampling using a questionnaire distributed to Waroeng Hotplate Odon visitors. The structural Equation Modeling (SEM) method is used to analyze the data. This research showed that 4 variables affect customer satisfaction and loyalty of Waroeng Hotplate Odon visitors, which are price, process and physical evidence. The satisfaction variable has a significant effect on consumer loyalty, which is reflected by consumers' willingness to make repeat purchases and recommend restaurants to other parties. In general, respondents feel satisfied and loyal to the restaurant. Based on the result of the study, the following strategies to increase customer loyalty of Waroeng Hotplate Odon are improving the quality of flavour, spiciness level, variety of the menu, offering menu with more affordable prices, improving restaurant’s layout and parking spaces, and implementing a service system based on Standard Operating Procedures (SOP).